Cigarette Smoke Exposure Induces Neurocognitive Impairments and Neuropathological Changes in the Hippocampus - Dobric, Aleksandar; De Luca, Simone N.; Seow, Huei Jiunn; Wang, Hao; Brassington, Kurt; Chan, Stanley M. H.; Mou, Kevin; Erlich, Jonathan; Liong, Stella; Selemidis, Stavros; Spencer, Sarah J.; Bozinovski, Steven; et al. (Frontiers in Molecular Neuroscience, 2022)
Background and objective: Cognitive dysfunction is present in up to ~61% of people with chronic obstructive pulmonary disease (COPD), with symptoms including learning and memory deficiencies, negatively impacting the quality of life of these individuals. As the mechanisms responsible for cognitive deficits in COPD remain unknown, we explored whether chronic cigarette smoke (CS) exposure causes cognitive dysfunction in mice and whether this is associated with neuroinflammation and an altered neuropathology. Methods: Male BALB/c mice were exposed to room air (sham) or CS (9 cigarettes/day, 5 days/week) for 24 weeks. After 23 weeks, mice underwent behavioral tests to assess working and spatial memory retention. At 24 weeks, mice were culled and lungs were collected and assessed for hallmark features of COPD. Serum was assessed for systemic inflammation and the hippocampus was collected for neuroinflammatory and structural analysis. Results: Chronic CS exposure impaired lung function as well as driving pulmonary inflammation, emphysema and systemic inflammation. CS exposure impaired working memory retention, which was associated with a suppression in hippocampal microglial number, however, these microglia displayed a more activated morphology. CS-exposed mice showed changes in astrocyte density as well as a reduction in synaptophysin and dendritic spines in the hippocampus. Conclusion: We have developed an experimental model of COPD in mice that recapitulates the hallmark features of the human disease. The altered microglial/astrocytic profiles and alterations in the neuropathology within the hippocampus may explain the cognitive dysfunction observed during COPD.